APPLICATION OF KARAKURI KAIZEN TO IMPROVE EFFICIENCY AND REDUCE WASTE IN THE PRODUCTION AREA - Maya Nurmayanti Uswatun Hasanah; Heru Darmawan; Rani Rahmadiyani (Bulletin of Engineering Science, Technology and Industry, 2026)
Competition in the manufacturing industry encourages companies to improve efficiency, productivity, and the smoothness of material flow. This study aims to analyze the implementation of Karakuri Kaizen in reducing waste in the material handling process on the die casting production line of PT AXZ. The material used to develop this article was taken from a thesis document containing the background, theoretical basis, methods, observation results, line balancing, a comparison of touching before and after improvement, and the bibliography. The research method used an applied approach with a quantitative descriptive design through field observation, interviews, documentation, literature study, work-time measurement, and before-after analysis. The results show that layout improvement and the use of the Karakuri Kaizen mechanism were able to reduce transportation and motion waste. The number of touches decreased from 17 times to 7 times, material handling cycle time became approximately 1 minute faster, CT irregular MP lastman improved by about 0.7 seconds, and manpower requirements were reduced from 4 operators to 3 operators. Line efficiency remained in a safe condition at 84.5% because the 60-second cycle time was still below the 71-second takt time. Thus, Karakuri Kaizen effectively supports a leaner, more ergonomic, and more productive production process without increasing electrical energy consumption.